THE INFLUENCE OF UNDERSTANDING ACCRUAL-BASED GOVERNMENT ACCOUNTING STANDARD, THE USE OF SAIBA APPLICATION, AND COMPETENCE ON THE EFFECTIVENESS OF MAKING FINANCIAL STATEMENT WITH MANAGEMENT COMMITMENT AS MODERATING VARIABLE IN THE WORK UNITS OF THE MINIS - Jannah, Nur (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the influence of understanding accrual-based government accounting standard, the use of SAIBA application, and competence on the effectiveness of making financial statement with management commitment as moderating variable in the Working Unit of the Minister of Religious Affairs as the work partner of KPPN, Tebing Tinggi. The population was 74 financial statement makers the consisted of PPK and SAIBA operators in the Working Unit of the Minister of Religious Affairs as the work partner of KPPN, Tebing Tinggi, and the samples were taken by using census sampling technique. Primary data were gathered by distributing 74 questionnaire sheets and 72 of them were returned and analyzed by using Structural Equation Modeling Partial Least Squares (SEM-PLS). The result of the research showed that understanding accrual-based government accounting standard, the use of SAIBA application, competence, and management commitment had positive and significant influence on the effectiveness of making financial statement. Management Commitment as moderating variable could not moderate the correlation between understanding accrual-based government accounting standard and the effectiveness of making financial statement, between the use of SAIBA application and the effectiveness of making financial statement, and between competence and the effectiveness of making financial statement.